MEMBANGUN MOTIVASI SISWA YANG MAMPU MEMANAJEMEN WAKTU DENGAN BAIK - Hanum Puspa Dhiani; Arif Siaha Widodo; Nurilah Hanum; Mutmainnah Mutmainnah; Ahmad Dimyati (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The development of technology and information that was increasingly fast and sophisticated brought positive and negative impacts to the millennial generation who were already fluent in using technology. This certainly would affect the millennial generation’s motivation to learn and time management which the majority of those generation are students. In order to make the students manage the time well, strategies were needed to find out the way for students who able to manage time well and to increase student motivation in carrying out their activities as students while utilizing time productively. Therefore, we hold Community Service (PKM) with the theme "Building Student’s Motivation Who Able to Manage Time Well". The target participants of this activity are students of SMK Bintang Nusantara, South Tangerang. The method of this Community Service is in the form of interactive seminars and sharing knowledges. The results of this activity are students able to arrange a schedule of daily activities and determine priorities. It is expected that the school, especially from the Guidance Counseling (BK) teacher, can continue to motivate, to guide, and to monitor students progress in managing their time effectively and efficiently.Keywords: interactive seminar, millenial generation, motivation, time management, sharing knowledges